UNC-89 (obscurin) binds to MEL-26, a BTB-domain protein, and affects the function of MEI-1 (katanin) in striated muscle of Caenorhabditis elegans - Wilson, Kristy J. (The American Society for Cell Biology, 2012)
The ubiquitin proteasome system is involved in degradation of old or damaged sarcomeric proteins. Most E3 ubiquitin ligases are associated with cullins, which function as scaffolds for assembly of the protein degradation machinery. Cullin 3 uses an adaptor to link to substrates; in Caenorhabditis elegans, one of these adaptors is the BTB-domain protein MEL-26 (maternal effect lethal). Here we show that MEL-26 interacts with the giant sarcomeric protein UNC-89 (obscurin). MEL-26 and UNC-89 partially colocalize at sarcomeric M-lines. Loss of function or gain of function of mel-26 results in disorganization of myosin thick filaments similar to that found in unc-89 mutants. It had been reported that in early C. elegans embryos, a target of the CUL-3/MEL-26 ubiquitylation complex is the microtubule-severing enzyme katanin (MEI-1). Loss of function or gain of function of mei-1 also results in disorganization of thick filaments similar to unc-89 mutants. Genetic data indicate that at least some of the mel-26 loss-of-function phenotype in muscle can be attributed to increased microtubule-severing activity of MEI-1. The level of MEI-1 protein is reduced in an unc-89 mutant, suggesting that the normal role of UNC-89 is to inhibit the CUL-3/MEL-26 complex toward MEI-1.